Optimalisasi Perkembangan Motorik Anak Melalui Permainan Tradisional: Studi Literatur Review Mengenai Aktivasi Gerakan Dan Proses Kerja Otak - Neng Widiya Puspitasari; Nurul Fajriati; Siti Nurfalah (Paidagogia: Jurnal Pengajaran dan Pendidikan, 2025)
This study examines the influence of traditional games on children's motor development as an important aspect of growing up. As children grow older, their gross motor skills improve, and traditional games play a significant role in stimulating this development. Games that use simple materials and reflect the culture of the community not only involve physical activity but also support children's cognitive and social development. The method used in this study was a Systematic Literature Review (SLR) to evaluate 20 qualitative and quantitative research journals. The study analyzed various forms of traditional games, such as jump rope, cricket, and congklak, which were shown to improve children's fine and gross motor skills, coordination, and social skills. The results of the analysis show that traditional games have a significant influence in improving children's motor skills, both at the early childhood education (PAUD) and primary school (SD) levels. From the literature review, it was found that traditional games provide extensive benefits for children's physical and social development. Thus, the integration of traditional games in physical education activities in schools is strongly recommended as a holistic and effective approach to support children's motor development.